ELECTRICAL RESISTIVITY FOR HYDRATION OF SEDIMENTED GYPSUM SLURRY - Chong, Colin Ka Liang (Universiti Malaysia Sarawak (UNIMAS), 2019)
The phenomenon of Flue Gas Desulfurization process increasingly produces gypsum waste as by-product requires better design and construction of impoundment, which is used as storage for the waste. The knowledge of sedimented gypsum slurry’s geotechnical properties is therefore vital in solving the problem. This project presents the experimental results to correlate the electrical resistivity of gypsum slurry to its water content and curing time. The electrical resistivity tests are performed on six samples of gypsum slurry with different water to gypsum ratio and the reading of resistivities are recorded at curing time predetermined, as per the ASTM standards. The analysis of results reveals that resistivity of the gypsum is solely dependent on its water content and the resistivity falls as the water content rises. The correlation developed and relationship found between electrical resistivity of gypsum slurry and its water content is then hoped to be extended with its strength behaviour.